SISTEM INFORMASI SURAT MASUK DAN SURAT KELUAR PADA BAGIAN ADMINISTRASI PEMBANGUNAN SEKRETARIAT DAERAH KABUPATEN INDRAGIRI HILIR - Rifky Rivaldi; Usman Usman; Samsudin Samsudin (Indragiri Islamic University, 2024)
Information technology is developing rapidly and expanding in various fields, namely to facilitate performance in daily activities, including managing incoming and outgoing mail. The Development Administration Section is a part of the Regional Secretariat of Indragiri Hilir Regency. In carrying out the duties of the Development Administration Section, we experienced problems in terms of correspondence. The correspondence system is still conventional, incoming and outgoing letters still need to be recorded in an agenda book, the volume of letters is large, making it difficult to search for files and store documents. And documents. And archives in the form of physical documents can be lost or damaged. Apart from that, if the authorized official is not present then the disposition of incoming letters or signing outgoing letters will be hampered because everything cannot be done online. Due to this problem, a correspondence system is needed for the Development Administration Section. This system manages incoming mail, outgoing mail, and employee and officer data. This information system was designed using the System Development Life Cycle (SDLC) method with a waterfall model. And implemented using the PHP programming language and XXAMP and MySql web servers for database management.